The Effects of Audience Behaviour on Football Players' Performance - Paul Calleja; Adele Muscat; Andrew Decelis (Shahid Bahonar University of Kerman, 2022)
Audience behaviour is an external factor which could influence an athlete's performance during a match due to the evaluative attitude which it might convey. One of the most common positive influences on a team's motivation can be attributed to a supportive and cheering audience. Contrastingly, jeering can be interpreted as negative influence. High emotions exchanged between the spectators and the players may also show the important ties which bind them together, and this can affect the players' behaviour on the field of play. This study focuses on how crowd behaviour in Maltese football influences the players' performance in the game. The influence of spectator behaviour on the psychological state of six male national senior football team members and six male national team youth players was analysed through data gathered from individual semi-structured interviews. Results show that both senior and youth players are influenced by variables of audience behaviour and feel pressured and anxious throughout matches.  Incentives for positive behaviour need to be introduced, together with sanctions for the breaking of rules, as well as slogans and placards placed in the stands for further awareness need to become the norm. If we are to curb societal issues such as racism and violence, the need for educational strategies is clear.